2019
DOI: 10.1055/s-0040-1701200
|View full text |Cite
|
Sign up to set email alerts
|

Management of Sub-Acute Exacerbation of Bronchial Asthma with Blatta orientalis: A Case Report

Abstract: Asthma is a chronic respiratory disease. It is an inflammatory condition of the lower airways that affects around 275–300 million people globally and 25 to 30 million people in India. It can attack all age groups and is characterised by recurrent attacks of breathlessness, wheezing and coughing, which may vary from person to person in severity and frequency. It is caused by inflammation of air passages, hypersensitivity to allergens, pulmonary oedema and congestion of lungs. This case report is an evidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Various published case reports on the treatment of psoriasis by homoeopathy have demonstrated encouraging results. 15 16 17…”
Section: Discussionmentioning
confidence: 99%
“…Various published case reports on the treatment of psoriasis by homoeopathy have demonstrated encouraging results. 15 16 17…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis of PP includes atopic dermatitis (history of hay fever and asthma), contact dermatitis (no silvery scale), lichen planus (involves the wrist and ankles with less scale), seborrheic dermatitis (greasy scale), onychomycosis, tinea corporis (thinner scale with potassium hydroxide preparation), pityriasis rosea, osteomyelitis and mycosis fungoides (less distinct lesion borders). [9][10][11][12][13][14] Homoeopathic literature review revealed a case study done on PP and homoeopathy on a 66-year-old male patient through individualised homoeopathic therapy Sulphur 1M along with the Sulphur-based cosmetic cream. The results were significant within the 4 months of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…9 A case report of 32-year-old female with sub-acute exacerbation of bronchial asthma treated with Blatta orientalis 30C showed significant improvement in Elizabeth Junipers ACQ Score and spirometry along with reduction in number of attacks after 6 months of treatment. 10 An experimental animal model study was conducted to evaluate the antiasthmatic and anti-anaphylactic activities of Blatta orientalis mother tincture (MT). This study showed significant protection against acetylcholine and histamine aerosol-induced bronchospasm in treated with Blatta Orientalis guinea pigs.…”
Section: Introductionmentioning
confidence: 99%